Analysis of Lampung Tourism Contents on Social Media (Comparative Study of Instagram Accounts @Lampuung and @Potraitlampung - Toni Wijaya; Hartoyo Hartoyo; Cory Wardani (Journal of Multidisciplinary Academic Business Studies, 2026)
Purpose: This research uses a comparative qualitative analysis of Instagram posts published between January and May 2025. This study applies Situated Data Analysis to understand how social media content is shaped by platform logics, actors, and audience expectations. The content categories, visual styles, narratives, and thematic emphasis were analyzed. Research methodology: This study uses a comparative qualitative analysis of Instagram posts published between January and May 2025. This study applies Situated Data Analysis to understand how social media content is shaped by platform logics, actors, and audience expectations. The content categories, visual styles, narratives, and thematic emphasis were analyzed. Results: Significant differences were found between the two accounts. While @lampuung serves as an institutional promoter with comprehensive destination coverage, @portraitlampung acts as a curator focusing on emotionally resonant and aesthetically optimized content. Nature, marine, culinary, and recreational tourism dominate because of their visual appeal and algorithmic compatibility, whereas cultural, health, sports, and ecotourism receive limited attention. Conclusions: The study concludes that Instagram content visibility is influenced by platform affordances and curatorial power, reflecting distinct actor positions and engagement strategies on the platform. Destination marketing strategies should go beyond aesthetic optimization and focus on narrative-driven representations that integrate culture and sustainable tourism. Limitations: The study analyzed posts only between January and May 2025 and focused on two Lampung-based accounts, which may not represent broader tourism content across different regions or countries. Contribution: Theoretical: This study extends the Situated Data Analysis to tourism content research. Empirical: Demonstrates how digital visibility is shaped by platform affordances and curatorial power. Practical: Tourism marketing strategies should prioritize cultural and sustainable tourism in digital promotion.